Geological Considerations in Dam Engineering - Farzin Salmasi; John Abraham (Novel Perspectives of Engineering Research Vol. 6, 2022)
Engineering geological studies are important in all stages of the implementation of a dam project. The failure and rupture of more than a third of dams worldwide is the result of poor engineering geological studies at the dam site, which is a clear demonstration of the importance of geology for the successful design of dam projects. A number of dams face problems during construction and operation. In Iran, the failure of some dams is quite obvious. The most obvious of them is the Lar Dam located northeast of Tehran. Although the reservoir capacity of the dam is approximately one billion cubic meters, since its operation in 1980, less than one-third of the reservoir has been filled. One of the first steps in the construction and design of dams that ensures the success of the dam is the correct choice of dam site. Since Iran is located on areas with high seismic activity, the construction of dams should be made with an understanding of how seismic activity may impact their stability. Existence of active faults near the dam site is one of the most important factors that should be considered. This factor can also affect the choice of dam type. This study provides an overview of geological considerations of dam construction and provides examples from Iran and other countries to demonstrate the importance of the issue. The geology of dam engineering includes a variety of topics with different specializations. The purpose of this study is to provide an overview of the importance of geological studies for dam designers. Reviewing these cases will provide civil and water engineers with a deeper understanding of the soil characteristics under the dam foundation will lead to better interaction between geological and civil engineers. In addition, some important studies of problematic dam construction in the world are mentioned in order to create a better understanding of the problem for the engineers involved in design team.